(untitled) (TAJ: Journal of Teachers Association, 2019)
Carcinoma of the urinary bladder (urothelial carcinoma) affects men more often than women at a ratio of 3:1 to 4:1. Besides many other invasive diagnostic tools, cytological examination of voided urine is the technique for diagnosis of urothelial carcinoma in its preclinical phase long before its cystoscopic & radiographic/ imaging recognition. In this study, a total of 57 were taken to see the diagnostic accuracy of voided urine cytology in the diagnosis of urothelial carcinoma. Out of 57 cases, 53 (92.99%) were given positive for malignancy and 4 (7.01%) were negative. Histologic diagnosis was 14 (24.56%) non invasive papillary tumors, 1 (1.76%) carcinoma in-situ and 42 (73.68%) invasive carcinomas. Of 14 grade II non invasive papillary tumors, 12(85.72%) were positive cytologically. Of 42 cases of invasive carcinoma, 2 were negative and 100% positive cytology was noted in 1 case of carcinoma in–situ. For all low-grade tumors, the sensitivity was about 85.72% and for all high-grade tumors, it was about 95.34% with a sensitivity of 100% and 95.24% for flat CIS and invasive carcinomas respectively. For all tumors the sensitivity was 92.99%.The specificity was 100% since there were no false positive cases. The diagnostic accuracy was 93% (approximately) Consistent with previously published data, this study showed the highest diagnostic accuracy with high grade tumors and lowest with low grade tumors with maximum invasion limited to the lamina propria. Voided urine cytology purely a non invasive, simple, cheap, easy to perform technique can be done as a first line cost effective method in the diagnosis of urothelial carcinoma particularly in a developing country like Bangladesh. TAJ 2010; 23(1): 59-66